In disentangling two species limits of Hechtia (Bromeliaceae: Hechtioideae) from Sierra Madre Occidental, a new species is discovered from Durango, Mexico - Ramírez-Morillo, Ivón; Carrillo-Reyes, Pablo; Tapia-Muñoz, José Luis; Ramírez-Díaz, Claudia J. (Phytotaxa, 2021)
Epitypes are proposed for two species of Hechtia: H. subalata and H. jaliscana, both endemic to Western Mexico. The holotypes of both species consist of fruiting specimens. While the female flowers of both species are extremely similar, the staminate ones are noticeable different: we select staminate vouchers as epitypes to clearly circumscribe both taxa. As a result of the delimitation of the concept Hechtia subalata and its geographical distribution, we identify a new species from Durango, Mexico, previously misidentified as Hechtia subalata: Hechtia marthae. We provide images portraying plant parts of all species, as well as photographs in habitat. Finally, assessments of the conservation status of the three species sensu IUCN criteria are included.